Nitridation of nanocrystalline TiO2 thin films by treatment with ammonia - Romero-Gomez, P; Rico, V; Espinos, J; Gonzalez-Elipe, A; Palgrave, R; Egdell, R (2011)
Nanocrystalline anatase (TiO2) thin films prepared by a physical vapour deposition method were nitrided by annealing in flowing NH3 at temperatures ranging between 650 °C and 700 °C. It was established that there was a narrow window of temperatures which allowed both incorporation of interstitial nitrogen into the films with retention of the anatase phase without chemical reduction and preservation of the characteristic nanocrystalline morphology. These optimally modified films responded to visible light in photowetting tests and showed the ability to degrade an organic dye under visible light irradiation. © 2011 Elsevier B.V. All rights reserved.